The acquiring serbian language as a native language - Radulović, Milica M (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2017)
This paper presents the process of acquiring Serbian language as a native language, from birth to pre-school age. The paper is based on the assertion that the same language development stages apply to all languages of the world and to all children of the world, and that there are two stages in speech development: pre-lingual and lingual. The pre-lingual stage is dominated by vocals. Hence, this stage is termed vocalisation stage. The transition from the pre-lingual to the lingual stage is marked by the occurrence of the first word, and this is so-called holophrastic stage. In the lingual stage the first utterances represent a vocal manifestation of a child expressed in the form of a meaningful word used for the purposes of communication or for the purposes of expressing a child´s reactions to his/her experience of reality. The paper presents the development order in the course of acquiring certain word categories, as well as phenomena which accompany speech development (omission, metathesis, adopting clusters). The author also discusses the manner of acquiring the case and verbal systems. Likewise, the paper deals with lexical and morphophonemic neologisms, which children produce spontaneously. The study of neologisms indicates something extremely important, and that is the manner in which a child acquires the grammar of his/her native language. The paper also emphasises the most significant language functions: significative (signifying), communicative (objective) and egocentric (private).
Keywords: language functions; child; lingual stage; pre-lingual stage; language acquisition; language; grammar